2014
DOI: 10.1016/j.atherosclerosis.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased urinary cystatin C indicated higher risk of cardiovascular death in a community cohort

Abstract: Increased urinary cystatin C indicated higher risk of cardiovascular death in a community cohort. Methods:The association between u-CysC and cardiovascular mortality was investigated in a Swedish community-based cohort of 604 men aged 78 years. During follow-up (mean 6.7 years), 203 participants died, of which 90 due to cardiovascular causes.Results: High u-CysC (>0.029 mg/mmol Cr) was associated with a more than 2-fold risk of cardiovascular death (multivariable hazard ratio for quintile 5 vs. 1: 2.5, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Cystatin C level was strongly linked with mortality risk in those with established coronary artery disease [29] or heart failure patients [30]. Moreover, Helmersson-Karlqvist et al [31] indicated that increased concentrations of urinary cystatin C were independently associated with a more than 2-fold risk of cardiovascular death. Several underlying mechanisms might be explained the association between elevated cystatin C level and excessive risk of mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Cystatin C level was strongly linked with mortality risk in those with established coronary artery disease [29] or heart failure patients [30]. Moreover, Helmersson-Karlqvist et al [31] indicated that increased concentrations of urinary cystatin C were independently associated with a more than 2-fold risk of cardiovascular death. Several underlying mechanisms might be explained the association between elevated cystatin C level and excessive risk of mortality.…”
Section: Discussionmentioning
confidence: 97%
“…This study focused on the day to day variation of three markers for proximal tubuli damage [6][7][8][9]. Many conditions may cause tubular injury including diabetes, infections, surgery, heart failure, burns, hypercalcemia and administration of drugs such as contrast media, antimicrobials, chemotherapeutics, analgesics and immunosuppressives [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Since spot urine samples were analyzed, it was reasonable to express results also as u-CYSC/u-CREAT ratio in order to exclude the effect of different hydration states (as it is reported by others) [4,8,[26][27][28]. However, it is future science group www.future-science.com known that in case of tubular damage the excretion of creatinine is also affected which may influence the urinary protein/u-CREAT values [29].…”
Section: Preliminary Reference Ranges Patients' Datamentioning
confidence: 99%